2011
DOI: 10.3390/polym3031268
|View full text |Cite
|
Sign up to set email alerts
|

Defensins: Potential Effectors in Autoimmune Rheumatic Disorders

Abstract: Abstract:Defensins are small cationic peptides with antimicrobial properties. They constitute a highly conserved innate immune defense mechanism across species. Based on the arrangement of disulfide-bonds, α-and β-defensins are distinguished in humans. Both types of defensin comprise several distinct molecules that are preferentially expressed at epithelial surfaces and in blood cells. In the last decade, multiple immunomodulatory functions of defensins have been recognized, including chemotactic activity, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…α-defensins are homologous peptides expressed by cells participating in the innate immune response including neutrophils, macrophages and intestinal Paneth cells [ 29 ]. In addition to their role in innate immunity, recent studies showed that α-defensins may also play a role in the pathogenesis of autoimmune diseases [ 30 ]. DEFA1-3 (α-defensins 1–3) increase secretion of pro-inflammatory molecules and enhance the presentation of costimulatory molecules on T-cells [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…α-defensins are homologous peptides expressed by cells participating in the innate immune response including neutrophils, macrophages and intestinal Paneth cells [ 29 ]. In addition to their role in innate immunity, recent studies showed that α-defensins may also play a role in the pathogenesis of autoimmune diseases [ 30 ]. DEFA1-3 (α-defensins 1–3) increase secretion of pro-inflammatory molecules and enhance the presentation of costimulatory molecules on T-cells [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…37 Finally, it should be mentioned that HNP-1 as an immunostimulatory molecule is chemotactic for naive CD45RA/CD4 T cells, CD8 T cells, immature dendritic cells, and monocytes. 38 So the capacity for 2Abz 23 S 29 to increase one cytokine and decrease another cytokine might depend on the accumulation of immune populations and their activity within the bladder during UTI infection. In the future, the antimicrobial and immune-modulatory effect of the test peptide can be strengthened by the addition of some type of comparison of the inflammatory cell population in the urine and bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies reported defective functions and abnormality in the maturation of neutrophils [12] and NK cells [13] in CVID patients, it would be interesting to evaluate if the low levels and frequencies of salivary α-defensins 1-4 we observed mainly in the CVID subgroup may be associated with the status of recurrent infections typically observed in these patients. It appears interesting to underline that immunomodulatory functions were suggested for the α-defensins, as well as their involvement in the communication between the innate and adaptive immune systems [49]. Indeed, it was demonstrated that α-defensins can transfer from neutrophils to memory B cells to exert their bactericidal activity against Streptococcus pneumoniae [50].…”
Section: α-Defensinsmentioning
confidence: 99%